2016
DOI: 10.22159/ijpps.2016v8i12.14841
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Docking and Anti-Proliferative Activity of New Series of 1-Methylsulphonyl-3-Indolyl Heterocycles

Abstract: <p><strong>Objective</strong>:<strong> </strong>The present work aimed to synthesize a new series of 1-methylsulphonyl-3-indolyl heterocycles and study their cytotoxic activity. In addition, we attempted to explore the mode of the interaction of anti-proliferative compounds with the active site of carbonic anhydrase IX (CA IX) theoretically <em>via</em> molecular docking study.</p><p><strong>Methods</strong>:<strong> </strong>Novel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Abo‐Salem and co‐workers reported the synthesis and antiproliferative activities of novel 1‐methylsulphonyl‐3‐indolyl pyrazoles ( 207 , 208 , 209 & 210 ) as shown in Scheme 35 [81] . The target compound 207 was synthesized by the reaction of 1‐methylsulphonyl‐3‐acetylindole ( 205 ) with substituted hydrazines followed by Vilsmeier–Haack formylation reaction.…”
Section: Direct‐linked Indole‐c3 Pyrazole Hybridsmentioning
confidence: 99%
“…Abo‐Salem and co‐workers reported the synthesis and antiproliferative activities of novel 1‐methylsulphonyl‐3‐indolyl pyrazoles ( 207 , 208 , 209 & 210 ) as shown in Scheme 35 [81] . The target compound 207 was synthesized by the reaction of 1‐methylsulphonyl‐3‐acetylindole ( 205 ) with substituted hydrazines followed by Vilsmeier–Haack formylation reaction.…”
Section: Direct‐linked Indole‐c3 Pyrazole Hybridsmentioning
confidence: 99%
“…Progesterone, dehydroisoandrosterone, epiandrosterone, and 3hydroxy-5a-androstan-17-one are some of the steroids that are widely used as a pharmaceutical prototype for constructing various biologically active compounds [19][20][21][22][23]. Furthermore, indole is a well-known natural compound attracts massive interest of researchers in the field of organic and medicinal chemistry, having a broad spectrum of pharmaceutical activities comprise antitumor, antimicrobial, antiinflammatory, antiviral [24][25][26]. Scientific research studies revealed that a combination of two different bioactive molecules is of great medicinal interest [27].…”
Section: Introductionmentioning
confidence: 99%
“…These bioactive molecules can efficiently overcome most of the pharmacokinetic disadvantage of classical drugs where they can launch two or more mode of action in parallel to restrain tumor growth [27]. Based on the information provided and as our work continues to synthesize new anticancer agents [25,26,[28][29][30], our efforts in this work have directed to synthesize a new series of thiazolo [4,3-b]-1,3,4-thiadiazoles united to steroid moieties to be exploited for further diversification and screened for anti-proliferative activity.…”
Section: Introductionmentioning
confidence: 99%
“…3-Pyrazolyl indoles as an important subset of 2 indole derivatives had exhibited their versatile synthetic values [3][4][5][6][7] and a broad spectrum of biological activities [8][9][10] such as antimicrobial 11 , anti-inflammatory 12 and antioxidant 13,14 . As a result, much effort has focused on the synthesis of 3-pyrazolyl indoles, mainly including the cyclocondensation of 1, 3-diketones and related derivatives with hydrazines [15][16][17][18][19][20][21][22] , the direct coupling of indole derivatives and pyrazole derivatives 23,24 , acid-catalyzed intramolecular cyclization reaction of N-propargylation of N-acetyl-N-tosyl-hydrazine 25 , and other procedures [26][27][28] . However, all the reported reactions are performed in organic medium and extremely toxic hydrazines appear as a main nitrogen source for most of reactions, which can lead to serious environmental and safety problems.…”
Section: Introductionmentioning
confidence: 99%